Companion Proceedings of the 36th International Conference on Software Engineering 2014
DOI: 10.1145/2591062.2591161
|View full text |Cite
|
Sign up to set email alerts
|

Functional programming for all! scaling a MOOC for students and professionals alike

Abstract: Massive open online courses (MOOCs) have launched a scale shift in higher education, with several individual MOOCs now boasting tens or hundreds of thousands of participants worldwide. Our MOOC on the principles of functional programming has more than 100,000 registered students to date, and boasts one of the highest rates of completion (19.2%) for its size. In this paper, we describe our experience organizing this popular MOOC, and demonstrate how providing innovative supporting tools (IDE plugins, testing fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 13 publications
0
9
0
3
Order By: Relevance
“…These findings suggest many people use MOOCs as a way to seek personal knowledge growth and are less interested in grades as an indication of achievement (DeBoer et al, 2014), which supports the literature which shows MOOC learners' motivation is less based on receiving a certificate of completion, but more on their personal objectives and learning behaviors (Fini, 2009;Kop, 2011;Milligan et al, 2013). The findings of this study further indicated that about two-thirds of the participants felt positive about their MOOC learning experience compared to face-to-face or other online courses (Miller et al, 2014), citing such reasons as flexible course structure accessible anywhere and at anytime, learning a new skill or topic, quality of course materials, active interaction, and learning from an expert. Such findings are consistent with other studies and reports indicating the benefits of MOOCs: enabling the massiveness and diversity of the participants, allowing anyone to take advantage of such learning opportunities regardless of time, pace, geographic locations, formal prerequisites, and financial hardship (Breslow et al, 2013;McAuley et al, 2010).…”
Section: Excitement and Reasons For Taking This Mooc And Perception Omentioning
confidence: 59%
See 1 more Smart Citation
“…These findings suggest many people use MOOCs as a way to seek personal knowledge growth and are less interested in grades as an indication of achievement (DeBoer et al, 2014), which supports the literature which shows MOOC learners' motivation is less based on receiving a certificate of completion, but more on their personal objectives and learning behaviors (Fini, 2009;Kop, 2011;Milligan et al, 2013). The findings of this study further indicated that about two-thirds of the participants felt positive about their MOOC learning experience compared to face-to-face or other online courses (Miller et al, 2014), citing such reasons as flexible course structure accessible anywhere and at anytime, learning a new skill or topic, quality of course materials, active interaction, and learning from an expert. Such findings are consistent with other studies and reports indicating the benefits of MOOCs: enabling the massiveness and diversity of the participants, allowing anyone to take advantage of such learning opportunities regardless of time, pace, geographic locations, formal prerequisites, and financial hardship (Breslow et al, 2013;McAuley et al, 2010).…”
Section: Excitement and Reasons For Taking This Mooc And Perception Omentioning
confidence: 59%
“…The study by indicated skills such as time management, goal setting, higher level of critical analysis, and being intrinsically motivated as influencing the level of engagement and active participation in open personal learning environments such as MOOCs. Emerging literature also showed some MOOC participants preferred the MOOC format over traditional campus face-to-face learning (Miller, Haller, Rytz, & Odersky, 2014), but also indicated learners' "mixed feelings" toward taking MOOCs, considering their experience both stimulating and frustrating (Mackness, Mak, & Williams, 2010;Zutshi et al, 2013). Given that the literature on MOOCs is emerging, evidence-based research is needed to understand why people take MOOCs, what aspects of MOOCs attract their participants, and the role MOOCs play as a form of online instruction.…”
mentioning
confidence: 99%
“…Para motivar e estimular a permanência dos alunos nos cursos são incorporadas ferramentas inovadoras que possibilitam maior interatividade (MILLER et al, 2014), técnicas de gamificação (VAN HENTENRYCK & COFFRIN, 2014) e de design baseado no modelo Carpe Diem (SALMON et al, 2015), além da utilização de grupos de estudo presenciais que não só alavancam a motivação e engajamento, mas também a aprendizagem profunda (LI et al, 2014;CHEN & CHEN, 2015). Ainda com foco no estímulo à permanência dos alunos, mas também buscando a melhoria do desempenho (KURSUN, 2016), algumas instituições, estão atribuindo créditos aos alunos que realizam MOOCs (ZIRGER et al, 2014), ação possível por meio da combinação da interação em sala de aula e avaliação supervisionada (JOSEPH & NATH, 2013).…”
Section: Principais Intervenções Para Superar Os Desafios Para Aplicaunclassified
“…Related Work With the rise of MOOCs the issue of scalable courses has been addressed by others as well. For example, Miller et al [6] describe the set-up for a course on functional programming principles in Scala, using cloudbased computing to grade the style and implementation of student submissions. However, they require that students install Scala, the Scala build tool sbt, and an IDE to get started.…”
Section: Automated Gradingmentioning
confidence: 99%